How information and communication technology drives carbon emissions: A sector-level analysis for China - Zhou, Xiaoyong; Zhou, Dequn; Wang, Qunwei; Su, Bin (Energy economics, 2019)
Understanding the carbon implications of information and communication technology (ICT) is critical for tackling climate change challenges in the digital era. This paper develops an embodied carbon analysis framework by integrating input-output approaches to explore the extent to which and how ICT drives carbon emissions at the sector level. With the proposed framework, we not only assess the carbon emissions embodied in various ICT subsectors but also reveal the formation and changing mechanism by identifying their source sectors, transfer paths, and economic drivers. Using China as a case study, we find that ICT sector is far from being environment-friendly while considering its embodied carbon impacts, which are dozens of times greater than the direct impacts. This is because ICT sector can induce significant amounts of emissions through its requirement for carbon-intensive intermediate inputs from non-ICT sectors. The electricity sector and basic material sectors (e.g. chemicals, metal, and non-metal) are the most important carbon sources, and are involved in major carbon transfer paths. The fast growth of embodied emissions in ICT sector is driven by the large-scale expansion of final demand for ICT products, although improvements in upstream production efficiency have largely slowed the growth. We suggest that integrated carbon management strategies incorporating mitigation measures for specific sectors, supply chains, and economic drivers are particularly required for addressing ICT-related carbon emission issues. •An integrated input-output analysis framework can assess the extent to which and how ICT sector drives carbon emissions.•ICT sector is far from being environment-friendly while considering its embodied carbon impacts.•Fast-growing embodied emissions are driven by the expanding final demand for ICT products.•An integrated carbon management strategy for mitigating carbon emissions induced by ICT sector is proposed.